Chemical constituents, radical scavenging activity and enzyme inhibitory capacity of fruits from Cotoneaster pannosus Franch. Issue 5 (18th April 2017) - Les, Francisco; López, Víctor; Caprioli, Giovanni; Iannarelli, Romilde; Fiorini, Dennis; Innocenti, Marzia; Bellumori, Maria; Maggi, Filippo
Abstract : Cotoneaster pannosus (Rosaceae) is a semievergreen shrub, producing globose dark red pomes, native to China and widely used as an ornamental plant all over the world. Abstract : Cotoneaster pannosus (Rosaceae) is a semievergreen shrub, producing globose dark red pomes, native to China and widely used as an ornamental plant all over the world. Despite its extensive cultivation, little information is available on the chemical composition and biological activities of its fruits. In this work, the analysis of the chemical composition of C. pannosus fruits, in terms of phenolic components, carotenoids and ascorbic acid by HPLC/DAD, HPLC/ESI-MS and MS/MS as well as in terms of macro- and micro-nutrients was performed. The fruits proved to be a good source of shikimic acid and caffeoylquinic acids, whereas β-carotene, pelargonidin-3- O glucoside and cyanidin-3, 5-rutinoside gave an important contribution to the color of the fruit. Both the polar and apolar fruit extracts showed noteworthy radical scavenger activity and inhibitory effects against monoamine oxidase A (MAO-A), tyrosinase (TYR) and α-glucosidase, making C. pannosus red pomes a promising candidate ingredient in functional foods and dietary supplements.